EFEKTIVITAS PENGEMBANGAN STRATEGI KOOPERATIF TIPE JIGSAW TERHADAP PENGUASAAN NILAI-NILAI MODERASI BERAGAMA DI MAS DAREL HIKMAH - Sunawir, Nur Wulandari; Risnawati, Risnawati; Miftahurrizqa, Miftahurrizqa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education of religious moderation values is an important aspect in shaping character and social harmony in the educational environment. This study aims to evaluate the effectiveness of the development of jigsaw-type cooperative strategies in increasing the mastery of religious moderation values in Mas Darel Hikmah. The research method uses a pseudo-experimental approach with a non-equivalent group design pre-test post-test. The subjects of the study were 1 teacher of MAS DAREL HIKMAH and 56 students with details of 1 class XII science and 1 class XII social studies. The data that has been collected is analyzed using the T-test (Independent Samples Test) technique. The research sample consisted of two groups: an experimental group that underwent learning with a jigsaw-type cooperative strategy, and a control group that followed conventional learning. Data was collected through tests of religious moderation values before and after the intervention, as well as student satisfaction questionnaires with learning. The results of the analysis showed that the jigsaw-type cooperative strategy was effective in increasing the mastery of religious moderation values, with a significant increase in the experimental group compared to the control group. The implication of this study is the importance of implementing learning strategies that encourage cooperation and understanding of the values of religious moderation in educational institutions. This study contributes to the development of curriculum and learning based on moderation values in Islamic educational institutions.